2012
DOI: 10.1136/jnnp-2011-300376
|View full text |Cite
|
Sign up to set email alerts
|

KOMET: an unblinded, randomised, two parallel-group, stratified trial comparing the effectiveness of levetiracetam with controlled-release carbamazepine and extended-release sodium valproate as monotherapy in patients with newly diagnosed epilepsy

Abstract: LEV monotherapy was not superior to standard AEDs for the global outcome, namely time to treatment withdrawal, in patients with newly diagnosed focal or generalised seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 26 publications
2
96
1
9
Order By: Relevance
“…Levetiracetam was significantly associated with five AEs out of which three -anger/aggression, nervousness/agitation, and depression -were confirmative [20][21][22][23][24]. Sleep disturbances so far have been reported only occasionally [21,25] and probably are not in the focus of physicians' attention.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Levetiracetam was significantly associated with five AEs out of which three -anger/aggression, nervousness/agitation, and depression -were confirmative [20][21][22][23][24]. Sleep disturbances so far have been reported only occasionally [21,25] and probably are not in the focus of physicians' attention.…”
Section: Discussionmentioning
confidence: 80%
“…In randomized controlled trials including valproic acid as treatment for patients with newly diagnosed epilepsy, tremor was reported spontaneously by patients most often with this AED [24,33].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are as yet no Class I studies comparing the efficacy of VPA with other AED in IGE, two large class III studies (SANAD B and KOMET trial) confirmed its good efficacy and tolerability in these syndromes, supporting VPA as the first choice in IGE 22 23…”
Section: Discussionmentioning
confidence: 99%
“…Both studies demonstrated that LEV was as efficacious as the other standard regimens. 4,5 The evidence in the paediatric population was generally positive. 3,4,6,7 At the opposite end of the spectrum, geriatric patients were also shown in a Class II study to benefit from LEV monotherapy.…”
Section: Levetiracetammentioning
confidence: 99%